Heat and mass transfer during lignocellulosic biomass torrefaction: Contributions from the major components-cellulose, hemicellulose, and lignin - Tanoue, K.-I. (MDPI AG, 2020)
The torrefaction of three representative types of biomass-bamboo, and Douglas fir and its bark-was carried out in a cylindrical-shaped packed bed reactor under nitrogen flow at 573 K of the reactor wall temperature. As the thermal energy for the torrefaction was supplied from the top and the side of the bed, the propagation of the temperature profile of the bed is a crucial factor for discussing and improving the torrefaction reactor performance. Therefore, the temperature and gas flow rate (vector) profiles throughout the bed were calculated by model simulation so as to scrutinize this point. The measured temperature at a certain representative location (z = 30 mm and r = 38 mm) of the bed was well reproduced by the simulation. The volume faction of the bed at temperatures higher than 500 K at 75 min was 0.89, 0.85, and 0.99 for bamboo, and Douglas fir and its bark, respectively. It was found that the effective thermal conductivity is the determining factor for this difference. The heat of the reactions was found to be insignificant. Â© 2020 by the authors.